Klatskin tumor (Review of literature) - I. V. Mayev; D. T. Dicheva; D. N. Andreyev; T. V. Penkina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. Article reviews of cumulated literature data on the rare form of cholangiocarcinoma in bifurcation of hepatic ducts and named after Gerald Klatskin.Key points. Obstructive jaundice at the absence of abdominal pain is leading clinical symptom of this disease. The histological pattern is represented by adenocarcinoma of acinar, tubular, trabecular, alveolar or papillary types. Bismuth-Corlette classification, that allows more precise differentiation of hepatic ducts lesion localization, is presented; diagnostic methods are discussed in details.Conclusion. Difficulties of diagnosis and verification of Klatskin tumor determine a broad field for differential diagnostics. By virtue of low frequency disease represents a serious problem in assessment of cholestatic syndrome origin.